Welding in aircraft structures - Apps, R. L.; Gourd, L. M.; Jubb, J. E. M. (College of Aeronautics, 1966)
The welding processes relevant to the welding of aircraft materials are briefly reviewed, together with those materials of present or future interest for aircraft structures. The problems of design for welding are also considered. It is concluded that the prospects for welding are more premising in materials other than light alloys, which win be used for high speed aircraft. In addition, further development of automatic welding machines and large heat treatment facilities is needed.